If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1(8x + -10) = -9 Reorder the terms: 13 + -1(-10 + 8x) = -9 13 + (-10 * -1 + 8x * -1) = -9 13 + (10 + -8x) = -9 Combine like terms: 13 + 10 = 23 23 + -8x = -9 Solving 23 + -8x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -8x = -9 + -23 Combine like terms: 23 + -23 = 0 0 + -8x = -9 + -23 -8x = -9 + -23 Combine like terms: -9 + -23 = -32 -8x = -32 Divide each side by '-8'. x = 4 Simplifying x = 4
| 2x+10+5=25x | | 11x-4=10x+10-6 | | 360=(5x+5)2x | | -110=-5(7-3x) | | 5(t-4)=36 | | 4x^2+5x-6(x^2+x-2)= | | 5=20+r | | 10-x-1(-2)-8+4x= | | 16.7x=79.49 | | 3/5x-4=12 | | 4y=-9x | | 65/2 | | (y-7)(y-7)(y-7)=6 | | v+10=-1 | | 8316=(14784)r(9) | | 4x-6(2x-3)= | | -7+4m=-5+6m | | 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 |